Եզնիկ Կողբացու «Եղծ աղանդոց» երկի դարձվածքները - Հարությունյան, Քնար (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены фразеологизмы, употребленные в труде Езника Кохбаци «Опровержение лжеучений». Он досконально изучен в арменистике, однако использованные в нем фразеологизмы не были также подробно исследованы. В труде Езника Кохбаци использованы 177 единиц фразеологизмов, из которых 114 представлены в словарях древнеармянского языка. К ним мы добавляем еще 63, не вошедших в словари. Структурный и морфологический анализ фразеологизмов приводит к заключению, что большинство из 177 фразеологических единиц — глагольные. По своей структуре большинство фразеологизмов (86,4%) двухкомпонентные. В работе «Опровержение лжеучений» Езник использовал наиболее распространенные в период написания труда фразеологические обороты. The article discusses the idioms in “Refutation of the Sects” by Yeznik of Kolb. Although this work has been thoroughly studied by Armenologists, the idioms used in it have not yet been studied in detail. 177 idioms are used in the “Refutation of the Sects”, of which 114 are presented in the dictionaries of the Classical Armenian language (grabar). To them we add 63 more, not included in the dictionaries. Structural and morphological analysis of these idioms leads to the conclusion that most of them are verbal. According to their structure, 86.4% of them are twocomponent. In his work, Yeznik of Kolb used the most widespread idioms of the fifth century.
Keywords: Պատմություն; Բանասիրություն